Menuju Literasi Gizi: Komponen Pengetahuan Gizi pada Program Edukasi Gizi Siswa Sekolah Dasar - Nuril Aiffa Dewantari; Ahmad Syafiq; Sandra Fikawati (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Nutrition knowledge is a fundamental base for determining attitude and practice in food choice. This study aimed to determine the magnitude of knowledge among elementary students. Analysis based on pre-test and post-test among elementary students who had been intervened by Gerakan Nusantara team. The intervention of nutrition education was held in 2014 to 2018 among 7113 selected elementary students in Indonesia. T-test of SPSS was used to analyze data. Standardization was held to determine the magnitude of change in each component of nutrition knowledge before and after nutrition education intervention. The result showed there was a significant change in nutrition knowledge after intervention p<0.05 from 2014 to 2018. The lowest magnitude of nutrition knowledge change was in 2014 (mean score=6.0±18.2). The lowest component of nutrition knowledge change was tumpeng balance nutrition guidelines dan and my plate food (mean score=2.3±1.4). This study showed that there was enhancement nutrition knowledge among students who were supported by their environment and the lowest magnitude of component knowledge was tumpeng balance nutrition guidelines dan and my plate food. The implementation of nutrition policy which was followed by effective media and method was necessary to be done to improve nutrition knowledge so that could affect attitude and practice among students.